1992
DOI: 10.3168/jds.s0022-0302(92)78125-9
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Limitation and Flow to Duodenum at Four Stages of Lactation. 1. Sequence of Lysine and Methionine Limitation

Abstract: Four Holstein cows with ruminal and duodenal cannulas were assigned to a 4 x 4 Latin square at each of four stages of lactation (peak, wk 4; early, wk 8 to 12; mid, wk 17 to 21; and late, wk 27 to 31). Treatments were duodenal infusions of 1) Met, 2) Lys, 3) Met plus Lys, and 4) casein; periods were 7 to 10 d. Quantities of DL-Met, L-Lys, and casein infused at the four stages of lactation were 12, 30, and 400; 12, 30, and 400; 10, 25, and 333; and 8, 20, and 266 g/d, respectively. Rations were composed of corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
120
1
17

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(149 citation statements)
references
References 27 publications
11
120
1
17
Order By: Relevance
“…Emmanuel and Kennelly (1984) found that 28% of the absorbed methionine is used for choline synthesis in lactating goats. The first limiting amino acid on corn, soybean meal, corn silage and alfalfa-based diets is usually methionine (Schwab et al, 1992;Rulquin et al, 1993). Armentano et al (1997) supplemented the diet of lactating cows with 10.5 g/day rumen-protected methionine and found a 1 g/kg increase in milk protein concentration and a 42 g increase in protein yield, although no milk yield response was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Emmanuel and Kennelly (1984) found that 28% of the absorbed methionine is used for choline synthesis in lactating goats. The first limiting amino acid on corn, soybean meal, corn silage and alfalfa-based diets is usually methionine (Schwab et al, 1992;Rulquin et al, 1993). Armentano et al (1997) supplemented the diet of lactating cows with 10.5 g/day rumen-protected methionine and found a 1 g/kg increase in milk protein concentration and a 42 g increase in protein yield, although no milk yield response was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The amount and availability of the most limiting amino acids in rumen undegradable protein play an important role in covering the AA requirements of high producing animals (Schwab et al, 1992). In the French system for prediction of lysine and methionine absorption (Rulquin and Verite, 1993), it is assumed that the AA profile of original feed protein is equal to the AA profile of undegraded feed protein, as found by Ganev et al (1979), Weakley et al (1983) and Teller et al (1985).…”
Section: Discussionmentioning
confidence: 99%
“…Otras de las causas de los resultados negativos al adicionar este aditivo se pueden atribuir a la etapa de la lactancia (Schwab et al, 1992), ya que su efecto positivo se registra, en su mayoría, a inicios de lactancia. En el presente experimento las vacas se encontraron en 138 días de lactancia como promedio (mediana lactancia), por lo que esta situación pudo afectar negativamente la respuesta al suplementar los animales con HMBTA.…”
Section: Discussionunclassified